2021
DOI: 10.1016/j.heliyon.2021.e08102
|View full text |Cite
|
Sign up to set email alerts
|

The degradation of textile industry dyes using the effective bacterial consortium

Abstract: The effluents from textile industries without proper treatment contains a remarkable amount of synthetic dyes which are harmful to the environment and a big challenge globally to degrade it with a eco-friendly way. Conventional methods are extremely energy-consuming, non-effective and generate a toxic sludge impacting the environment. Several microorganisms can be utilized to treat these effluents. The research deals with five bacteria isolated from textile effluent and their consortium for the biodegradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 44 publications
1
18
0
1
Order By: Relevance
“…However, the study found that the bacterial strains were affected by high Mordant black 11 concentrations, noting a decrease in dye degradation with an increase in dye concentration from 50mg/l-150 mg/l, with maximum degradation observed at 50 mg/l. Similar studies [ 89 , 90 ] have shown that Increased dye concentration in the culture medium creates a toxic environment that leads to enzyme inhibition, consequently decreasing the dye degradation efficiency. Other studies have also been reported [ 91 , 92 , 93 ] showing that biofilms perform better in dye degradation when compared their free forms under similar conditions.…”
Section: Latest Advances In Bacterial Dye Degradationmentioning
confidence: 67%
“…However, the study found that the bacterial strains were affected by high Mordant black 11 concentrations, noting a decrease in dye degradation with an increase in dye concentration from 50mg/l-150 mg/l, with maximum degradation observed at 50 mg/l. Similar studies [ 89 , 90 ] have shown that Increased dye concentration in the culture medium creates a toxic environment that leads to enzyme inhibition, consequently decreasing the dye degradation efficiency. Other studies have also been reported [ 91 , 92 , 93 ] showing that biofilms perform better in dye degradation when compared their free forms under similar conditions.…”
Section: Latest Advances In Bacterial Dye Degradationmentioning
confidence: 67%
“…ON934589.1 reached a maximum of 91.54% at 303 °C. Conversely, as the temperature rose to 313 °C, the decolorization activity decreased (53%) due to the loss of cell viability or inactivation of the decolorizing enzymes 65 . Arunprasath et al 4 observed that the optimum temperature (30 °C) was the optimum temperature for the decolorization (92%) of Malachite green dye by Lasiodiplodia strains.…”
Section: Resultsmentioning
confidence: 99%
“…ON934589.1 reached a maximum of 91.54% at 303 °C. Conversely, as the temperature rose to 313 °C, the decolorization activity decreased (53%) due to the loss of cell viability or inactivation of the decolorizing enzymes [71]. Arunprasath et al [2,72] observed that the optimum temperature (30 °C) was the optimum temperature for the decolorization (92%) of malachite green dye by Lasiodiplodia strains.…”
Section: Interactive Impact Of Temperature On Mg Dye Decolorizationmentioning
confidence: 99%